Correction to: Socioeconomic inequalities in suicide mortality before and after the economic recession in Spain - Carme Borrell; Marc Marí-Dell'Olmo; Mercè Gotsens; Montse Calvo; Maica Rodríguez-Sanz; Xavier Bartoll; Santiago Esnaola (BMC, 2019)
It has been highlighted that the original article